Identifikasi Potensi Akuifer Menggunakan Uji Resistivity Ves (Vertical Electrical Sounding) (Studi Kasus: Desa Pohijo, Sampung-Ponorogo) - Asmaranto, Runi (Fakultas Teknik, Universitas Brawijaya, 2014)
The problems occurred at the Kangkungan-Pohijo are not available surface water irrigation needs. BPP FT-UB as a community service agency conducting a relief estimating groundwater flow wich is done to determine potential for subsurface flow. If found potential of groundwater, useful to development irrigation potential so increasing harvest productivity. The aim of study is determine locations which have groundwater flow potential to support pump irrigation. The result of this study shown that point 4 is the best potential of groundwater flow than other location. This location was also its existence still on the region of â€œbengkok desaâ€, so it is recommended as the first alternative. The point-2 was recommended as an a second alternative. The response of residents of Pohijo village was very enthusiastic in order to realize procurement pump groundwater.Keyword: aquifer, transmisivity, resistivity, vertical electrical sounding, configuration